Growth conditions of graphene grown in chemical vapour deposition (CVD) - Mohamad Shukri Sirat,; Edhuan Ismail,; Hadi Purwanto,; Mohd Asyadi Azam Mohd Abid,; Mohd Hanafi Ani, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The fabrication of high quality graphene has become the main interest in current chemical vapour deposition (CVD) method due to the scalability for mass production of graphene-based electronic devices. The quality of graphene is determined by defect density, number of layers and properties changed such as electron mobility, transparency and conductivity as compared to the pristine graphene. Here, we did a study on the effects of reaction conditions such as methane, CH4 concentration and deposition time towards the quality of graphene produced. We found that by lowering both CH4 concentration down to 20% and deposition time to 5 min, a better quality graphene was produced with higher I2D/IG ratio of 0.82 compared to other reaction condition. Through the analysis, we concluded that there are two important parameters to be controlled to obtain high quality graphene.